COMPARATIVE STUDY OF CARDIOPROTECTIVE EFFECT OF VARIOUS DIAMETER AND COMPOSITION LIPOSOMES DURING REPERFUSION OF THE ISOLATED RAT HEARTS AFTER NORMOTHERMIC ISCHEMIA - Ya. G. Toropova; R. A. Mukhamadiyarov; A. S. Golovkin (Бюллетень сибирской медицины, 2013)
The wide application of cardiac surgery using the aorto-pulmonary bypass technique needs the development of new drugs, capable to minimize the heart damaging during ischemia and reperfusion. But the direct delivery of drugs into the damaged tissues and cells is a big problem. The liposomes as unique transport system can be used to solve this problem.The aim of the study was to evaluate the influence of "empty" liposomes of various diameter and the liposomes of different composition on the myocardium contractile function which has underwent the ischemia and the subsequent reperfusion. The obtained results allowed us to make the conclusion that liposomes of 50 nanometers in diameter are most effective to cardiac protection versus liposomes of 100 nanometers.Inclusion the emoxipine into the composition of liposomes provide the best results on contractile function of an ischemic myocardium.